La formation au métier d’enseignant de français à l’épreuve du distanciel - Mohamed Hattab; Gamal El Hak Fari Bouanani (Multilinguales)
This article examines the issue of the online training and more particularly the blended learning not from a pragmatic point of view (benefits and limitations), nor from an ideological point of view (education as commodity) but from an engineering and didactic point of view. We aim to evaluate the online training system for the future teachers of French as a Foreign Language in Algeria and this in relation to the evolution of blended learning systems throughout the world.